2010
DOI: 10.1002/ptr.3097
|View full text |Cite
|
Sign up to set email alerts
|

Berberine elicits anti‐arrhythmic effects via IK1/Kir2.1 in the rat type 2 diabetic myocardial infarction model

Abstract: The purpose of this study was to explore the anti-arrhythmic mechanisms of berberine in diabetic rats with myocardial infarction. Sixty rats were divided into four groups: (1) normal control; (2) myocardial infarction group (MI); (3) Type 2 diabetes with myocardial infarction group (T2DM+MI); and (4) Type 2 diabetic with myocardial infarction berberine-treated group (BBR). Berberine (60 mg/kg/day) was administered after coronary artery ligation in the T2DM+MI group for 14 days. Currents were measured using who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Pertinently, levels of Kir2.1 have been shown to be depressed in rat models of both MI and T2DM with MI(Wang, Yu, Fu, Li, & Sun, 2011) although the investigators…”
mentioning
confidence: 96%
“…Pertinently, levels of Kir2.1 have been shown to be depressed in rat models of both MI and T2DM with MI(Wang, Yu, Fu, Li, & Sun, 2011) although the investigators…”
mentioning
confidence: 96%
“…Moreover, our previous studies demonstrated that BBR improves ischemic arrhythmias through influencing Ito and Ica currents in diabetic rats . BBR reduced the incidence and duration of arrhythmias induced by myocardial infarction (Wang et al, 2011). In addition, Li et al reported that BBR alleviates cardiac ischemic and reperfusion injury and cardiac remodeling in diabetic rats (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Berberine (BBR) is a type of isoquinoline alkaloid that is isolated from a variety of plants, such as Coptis chinensis (Chinese goldthread), Berberis vulgaris (barberry), and Phellodendron amurense (Amur corktree) (Cicero and Baggioni, 2016). BBR reduced the incidence and duration of arrhythmias induced by myocardial infarction (Wang et al, 2011). Moreover, our previous studies demonstrated that BBR improves ischemic arrhythmias through influencing Ito and Ica currents in diabetic rats .…”
Section: Discussionmentioning
confidence: 99%
“…Loubele et al (24) reported that the inhibition of apoptosis and inflammation contributes to the rehabilitation of myocardial ischemia/reperfusion injury. In addition, Wang et al (25) demonstrated that berberine acts as anti-arrhythmic drug in a rat type ІІ diabetic myocardial infarction model by repressing the inward rectifier potassium channel 2. Berberine also exhibits anti-infl amma-.…”
Section: Discussionmentioning
confidence: 99%